Compressive Strength Of Concrete The Time Setting Of Application Of Plastiment® P-121 Additive Mixture - Alfina Maysyurah; Achmad Rusdi; Albert Didik Setyo Purwantoro (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Islam Lamongan, 2024)
Infrastructure growth requires large quantities of concrete, a problem of concern distance between the batching plant and location of different casting locations, the process mixing and transporting to casting location requires time that can exceed the cement setting time. Plastiment helps improve the strength, durability and general quality of concrete. This research aims to determine the compressive strength of concrete at setting times of 60, 90 and 120 minutes using 150 mm x 300 mm specimens with variations in addition of plastiment of 0.20% and 0.40% of the cement weight. Primary data the form of material testing data and concrete compressive strength for each variation and secondary data is in the form of additives and the properties of cement used. The test results show that the compressive strength of concrete at 60, 90 and 120 minutes by adding Plastiment® P-121R at a variation of 0.20% is 17.55, 18.12 and 18.85 MPa while giving a dose of 0.40% is 17 .27, 19.82 and 22.08 MPa. Addition of plaster can meet the slump value requirements at each time variation and in contrast to normal concrete the slump value is not met at each time variation with the concrete having dried during mixing.